1975
DOI: 10.1002/pssb.2220700239
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of Force Constant Change of Mössbauer 119Sn Impurity Nuclei in Palladium Host

Abstract: Precision measurements are made of the second order Doppler shift and absorption areas of the Mossbauer line of ll9Sn, present as a dilute impurity in palladium lattice, over a range from liquid helium temperature to about 750 O K . The weighted mean temperatures have been determined from the moments w ( -2 ) , w ( -l), w ( + l), and w( + 2 ) of the phonon frequency distribution in the palladium lattice as seen by the Mossbauer l19Sn impurity atoms. Assuming a Debye spectrum, ratios of the impurity-host t o ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Our results are further supported by the analysis of Grow et al [(i], who found the value of A'/A = 0.44 with no evidence of a localized mode in the IO' Pd: IlsSn system. I n addition, Puri and Gupta [19], analysing their measurements of f in the framework of the Debye model got X'/A = 0.47, which obviously is comparable to our resuit. Van Landuyt et al reported nieasurcmcnts of f-values up to 300 K and assumed, quite explicabIy, that there is no need for any correction for anharmonicity, since the Debye temperature of Pd is 275 K. However, in view of the available measurcments of the system lo7Pd:11%n up to 729 K by Pnri and Gupta [19] an attempt to calculate the recoilless fraction over the entire temperature rangc, neccssitatcd the incorporation of anharmonicity.…”
Section: Results Arid Discussionsupporting
confidence: 85%
“…Our results are further supported by the analysis of Grow et al [(i], who found the value of A'/A = 0.44 with no evidence of a localized mode in the IO' Pd: IlsSn system. I n addition, Puri and Gupta [19], analysing their measurements of f in the framework of the Debye model got X'/A = 0.47, which obviously is comparable to our resuit. Van Landuyt et al reported nieasurcmcnts of f-values up to 300 K and assumed, quite explicabIy, that there is no need for any correction for anharmonicity, since the Debye temperature of Pd is 275 K. However, in view of the available measurcments of the system lo7Pd:11%n up to 729 K by Pnri and Gupta [19] an attempt to calculate the recoilless fraction over the entire temperature rangc, neccssitatcd the incorporation of anharmonicity.…”
Section: Results Arid Discussionsupporting
confidence: 85%